Subterranean pupation: a refuge for non-target species from a prospective biological control agent of the avian vampire fly in Galapagos - Ismael E. Ramirez; Alyssa T. Gooding; Katherine A. Albán; Saúl J. Aguirre; Paolo Piedrahita; Charlotte E. Causton; George E. Heimpel (BioControl, 2025)
The invasive avian vampire fly, Philornis downsi (Diptera: Muscidae), poses a significant threat to Darwin's Finches and other endemic bird species in the Galapagos Islands, and the importation of specialized natural enemies is a promising strategy for its long-term control. The parasitoid Conura annulifera (Hymenoptera: Chalcididae) has received the most attention as a potential biological control agent thus far, including studies assessing its potential to attack non-target species. The potential native and endemic non-target species that are hypothetically most at risk from a release of C. annulifera are those closely related to P. downsi, which include carrion flies in the families Calliphoridae, Muscidae, and Sarcophagidae. In other parts of the world, many of the species that belong to these families pupate in the soil, and since C. annulifera is an obligate pupal parasitoid, we hypothesized that subterranean pupation would constitute a spatial refuge from parasitism, lessening the risk of non-target effects. We thus investigated the burrowing behavior of carrion flies that are endemic and native to Galapagos using introduced flies as surrogates when we could not locate related endemic or native species. We also evaluated the ability of C. annulifera to locate and attack underground puparia of these species. Our trials revealed that, of nine species of carrion fly species tested, eight exhibited subterranean pupation. This included the Galapagos endemic sarcophagids Sarothromyiops dasycnemis and Galopagomyia inoa . Notably, C. annulifera females did not exhibit burrowing behavior and thus were not able to locate or attack subterranean puparia. Our study suggests a low level of risk to endemic and native non-target fly species in Galapagos since many of these species are known to or are expected to pupate within the soil.